International model for analysis of agricultural commodities and trade-standard IFPRI multimarket model (IMPACT-SIMM): Technical description for version 1 - Robinson, Sherman; Anderson, Lillian; Dunston, Shahnila; Gabriel, Sherwin; Komarek, Adam M.; Mason-D’Croz, Daniel; Sulser, Timothy B. (International Food Policy Research Institute, 2021)
The International Food Research Institute’s International Model for Analysis of Agricultural Commodities and Trade (IMPACT) supports analysis of long-term challenges and opportunities for food, agriculture, and natural resources at global and regional scales. IMPACT is continually being updated and improved to better inform the choices that decisionmakers face today. This document describes a new country-level version of the model. IMPACT-SIMM (International Model for Analysis of Agricultural Commodities and Trade–Standard IFPRI Multimarket Model) is a partial equilibrium, multi-market, simulation model of the production, supply, and demand of agricultural commodities within a country or group of countries. It simulates the operation of agricultural markets, solving for equilibrium prices within a country and, in multi-country mode, global markets. It is designed to be a “portable” and potentially open-source version of the IFPRI (International Food Research Institute) IMPACT3 model documented in Robinson et al. (2015). IMPACT-SIMM shares model specification, equations, and computer code with IMPACT3, but is designed to be more flexible in application. It allows users to specify a standard multi-market model at any level of aggregation by commodities and countries by changing data inputs, without any change in model code. This model system supports longer-term scenario analysis to provide researchers and policymakers with a flexible tool to assess and compare the potential effects of changes in biophysical systems, socioeconomic trends, technologies, and policies at the level of individual countries or groups of countries.